2015
DOI: 10.1080/20504721.2015.1069528
|View full text |Cite
|
Sign up to set email alerts
|

Police understandings of restorative justice—the impact of rank and role

Abstract: The issue of a disparity between restorative justice theory and restorative practices has been widely examined. Daly (2002:55-79) argues gaps are to be expected because there is a lack of understanding around what restorative justice is. This research uses qualitative data from four focus groups and ten interviews (n=41) to examine police officer's understandings of what restorative justice is, and equally as important, what it is not. Overall findings suggest a continuum of understanding exists across a poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 19 publications
4
23
0
1
Order By: Relevance
“…From the women's narratives in the qualitative study, however, and as found in previous research, there seemed to be variation in the type of facilitation and RJ they experienced, including in its quality (Shapland et al, 2017;Cutress, 2015;Stockdale, 2015; Criminal Justice Joint Inspection, 2012) alongside general confusion for offenders over the place of RJ in the CJS (Criminal Justice Joint Inspection, 2012).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…From the women's narratives in the qualitative study, however, and as found in previous research, there seemed to be variation in the type of facilitation and RJ they experienced, including in its quality (Shapland et al, 2017;Cutress, 2015;Stockdale, 2015; Criminal Justice Joint Inspection, 2012) alongside general confusion for offenders over the place of RJ in the CJS (Criminal Justice Joint Inspection, 2012).…”
Section: Discussionmentioning
confidence: 56%
“…A 2012 report on the uses of RJ by police, probation and youth offending teams in six counties in the UK revealed some further concerns, including 'widespread inconsistency in the implementation of RJ initiatives across the whole criminal justice system, with conflicting terminology and a lack of understanding of the principles of RJ' (Criminal Justice Joint Inspection, 2012:11). In sum, research on police-led RJ in the UK has found that as RJ for low-level offences is up to the discretion of, and facilitated by, individual officers, when their understanding of RJ is lacking, then this is evidenced in their practice (Shapland, Crawford, Gray & Burn, 2017;Cutress, 2015;Stockdale, 2015;Criminal Justice Joint Inspection, 2012). At its worst, this may include net-widening (Criminal Justice Joint Inspection, 2012;O'Mahony and Doak, 2004) and ignoring the 'voluntary' aspect of RJ (Shapland et al, 2017: 22).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have noted that the understandings of police organisational culture rely predominantly on older ethnographic studies, and often predates many significant transformations in policing, such as RJ (Brough et al, 2016). Stockdale (2015) has provided some insight into the interaction between RJ and police culture and how police rank affects officer understanding of RJ. She found that police understandings of RJ varied, with officers in different ranks being focused on different aspects of the restorative justice process.…”
Section: Restorative Justice and Policementioning
confidence: 99%
“…The differences between the traditional justice system and restorative justice has raised questions and concerns regarding the ability of criminal justice practitioners (particularly police) to balance the competing goals of RJ and the traditional criminal justice system (Crocker, 2016). However, it appears that frontline officers generally view restorative justice as a viable option for both youth and adult offenders (Crocker, 2013;Stockdale, 2015), while earlier studies have found that police often did not have a clear understanding of RJ philosophies, and viewed it as appropriate for first time, less serious, non-violent offenders (Abramson, 2003). Throughout their duties, frontline officers consider discretionary factors that are available to them when making decisions regarding RJ.…”
Section: Restorative Justice and Policementioning
confidence: 99%
See 1 more Smart Citation